General practitioners’ opinions of generative artificial intelligence in the UK: An online survey - Anna Kharko; Carolina Garcia Sanchez; Josefin Hagström; Jens Gaab; Cosima Locher; Brian McMillan; David Sundemo; Charlotte Blease (Digital Health)
Background The rapid rise of large language model-based generative artificial intelligence (AI) tools, such as chatbots and AI scribes, has prompted interest in their clinical applicability. This study examined the perspectives of general practitioners (GPs) in the UK regarding the impact of generative AI on clinical practice. Methods In January 2025, a national online survey of 1005 GPs, stratified by region, was administered via the UK's largest clinical marketing platform. The survey gathered data on attitudes towards generative AI, its perceived effects on clinical tasks, care delivery and respondent demographics. Group differences and correlations between opinions and respondent characteristics were analysed. Results Among the 1005 respondents, 50% were male, 54% aged 46 or older, and 83% practised in England. Only 11% were encouraged by their employer to use generative AI tools, and 5% had received training. Most agreed that AI could improve documentation (69%) and patient information gathering (57%), and 59% expected increased efficiency in care. A similar proportion (59%) anticipated that patients may rely on AI instead of seeking medical care. The majority (79%) agreed that training is needed, while 71% disagreed that AI could enhance empathic communication. Male GPs were more likely to view AI as beneficial across tasks, while female GPs more often emphasised training needs. Older GPs expressed concern about potential inequities stemming from AI use. Conclusions While GPs were cautiously optimistic about generative AI – particularly for documentation and data collection – scepticism persisted. In particular, around empathy and equity, highlighting the need for guidance on AI integration into primary care.